Sex differences in predictors and outcomes of camouflaging: Comparing diagnosed autistic, high autistic trait and low autistic trait young adults. (February 2023) - Milner, Victoria; Mandy, Will; Happé, Francesca; Colvert, Emma
Many autistic individuals camouflage socially atypical behaviours. Evidence suggests autistic females camouflage more than autistic males. Although camouflaging may confer some benefits, it is also associated with negative outcomes including poorer mental health and well-being. Those with high autistic traits but no clinical diagnosis are not seldom included in camouflaging research, therefore we cannot ascertain whether camouflaging plays a role in the underdiagnosis of autistic females. Data from young adults with a diagnosis of autism ( n  = 78), high autistic traits but no diagnosis ( n  = 177) or low autistic traits ( n  = 180) revealed autistic females reported camouflaging significantly more than other groups. Males and females with low autistic traits reported significantly lower camouflaging than high trait and diagnosed groups. Loneliness was a key predictor of camouflaging for the diagnosed group only. Camouflaging was found to predict lower psychological quality of life for the diagnosed group, and lower social quality of life for the high trait and low trait groups. Overall, findings indicated that, although all groups reported camouflaging, the motivations for doing so may be different for diagnosed autistic individuals. It is important for stakeholders and society to improve understanding of autism and acceptance of atypical behaviour to alleviate possible negative outcomes associated with camouflaging. Lay Abstract: Many autistic people use strategies that help them adapt in social situations and hide behaviours that may seem different to non-autistic individuals – this is called camouflaging. Camouflaging may help autistic people fit in socially; however, it might also lead to poorer well-being. It has been suggested that autistic females camouflage more than autistic males. This article explored differences between males and females who have an autism diagnosis, have characteristics of autism but no diagnosis and those with few autistic characteristics. It is important to include these groups as camouflaging may make it more difficult to get an autism diagnosis and therefore make it less likely a person will receive support. We found that autistic women camouflaged more than all other groups. The group with few autistic characteristics (males and females) camouflaged the least. Loneliness was found to be a possible reason for camouflaging for the diagnosed autistic group only. In terms of outcomes related to camouflaging, it was found that those who camouflaged most had a lower quality of life; this was true of all groups. This tells us that there may be different reasons to camouflage, and different outcomes related to camouflaging for those with many characteristics of autism (including those with a diagnosis), and those with few. It is important that clinicians, teachers, parents and other stakeholders are aware of the negative outcomes associated with camouflaging so that more support can be provided for those who need it.